Mig welding of dissimilar metal (steel and aluminium) - Mohd Azizul Hafiz, Abdul Sani (2012)
Tailor welded blanks (YWBs) is a method used in automotive industries that offer an excellent opportunity to reduce manufacturing costs, decrease vehicle weight and improve the quality of sheet metal stamping. In this project, the objective is to study welding parameters used in joining two dissimilar metals. Mild steel and aluminium with thickness both 3mm was weld together using MIG welding with tailor welded blanks method. Voltages used in this project are 15.5, 17.5 and 20.5 V with feed speed of 65, 90, and 115 mm/min. The joints were evaluated by mechanical testing and metallurgical analysis. Microstructural analyses were done using metallography, microhardness testing and optical microscope. Result of these analysis suggested that failure were seen at the weld area of the joint. Further, at the fusion zone were form intermetallic compound layer that soft, brittle and low in mechanical strength.